Trancendence of Woman Existence through the Character of Shirayuki in the Anime Akagami No Shirayukihime - Aprilian, Neisya Fouriesta; Arianingsih, Anisa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Akagami no Shirayukihime (2015) features a female character named Shirayuki who actively shapes her identity through her actions. This research aims to analyze transcendence as a manifestation of women’s efforts to demonstrate their existence and ability to shape their own identity. The research applies a qualitative descriptive method by examining dialogues, character interactions, and selected scenes from the anime as the primary data source. The analysis is based on Simone de Beauvoir’s Existentialist Feminism theory, particularly the concept of transcendence, which explains women’s efforts to move beyond passive and socially imposed roles. The findings indicate that Shirayuki portrays transcendence through her independence and determination in making life choices. The findings indicate that Shirayuki portrays transcendence through her independence and determination in making life choices. She refuses forced marriage and rejects being treated as an object of male authority. In addition, she shows courage by leaving her hometown to pursue a better future. Shirayuki also develops her intellectual abilities through her dedication to studying herbal medicine and working as an apothecary. Her competence in solving medical problems and helping others demonstrates that women are capable of contributing meaningfully to society through knowledge and skill. Conclusion, Shirayuki’s character represents a woman who transcends patriarchal limitations through freedom, work, knowledge, and responsibility. This study highlights that Akagami no Shirayukihime offers a positive representation of female existence in anime, where women are portrayed as active subjects capable of defining themselves and contributing meaningfully to society.